B249 Continuous spinal anaesthesia and peripheral nerve block – a winning combination in severe aortic stenosis. (11th August 2022) - Sales, F; Pereira, C; Félix, F; Cunha, M
Abstract : Background and Aims: The main goals when managing patients with severe aortic stenosis are maintaining normal sinus rhythm and avoiding hypotension. Both general anesthesia and single-shot spinal are associated with significant hemodynamic changes, making them less than ideal options for these patients. 1, 2 Methods: We report the successful use of continuous spinal anesthesia in a frail patient with severe aortic stenosis waiting for Transcatheter Aortic Valve Implantation (TAVI). An 83-year-old woman, ASA IV, was scheduled for urgent non-cemented hip hemiarthroplasty due to a femoral neck fracture. Her medical history included severe aortic stenosis (valve area of 0.50 cm2, mean valve gradient of 33mmHg), heart failure, coronary artery disease, atrial flutter, hypertension, diabetes, bilateral carotid stenosis, COPD, and recent pneumonia. Results: Once in the theatre, standard monitoring was started, and a brachial arterial line was placed. A femoral nerve block was performed with 0, 5% ropivacaine (20 mL). An intrathecal catheter was placed and small doses of levobupivacaine 0, 5% (up to 4mg) were administered (8, 5mg total). A low-dose background infusion of phenylephrine was started at the time of intrathecal administration. The patient remained hemodynamically stable and comfortable throughout the procedure. The catheter was removed at the end of the surgery. Postoperative care continued in the level II unit for two days, with no complications. Postoperative pain was easily controlled with paracetamol and low-dose tramadol. Conclusions: Patients with severe aortic stenosis remain a challenge for anesthesiologists when presenting for orthopedic surgery. Continuous spinal anesthesia with peripheral nerve block is a safe and effective technique for these patients.